NILAI PENDIDIKAN ANAK DALAM KELUARGA SUPIR ANGKOT DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - ", Nurhafizah; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in the Rumbai Coastal Coastal District. The purpose of this study was to find out the value of children's education for parents of public transportation drivers in Rumbai Pesisir District. The topic of this research focus is the perception of public transportation drivers on children's education in Rumbai Pesisir District. Sampling techniques are nonprobability sampling and set a sample of 80 people. The author uses quantitative methods and data instruments are observation, questionnaires and documentation. Research conducted in Pekanbaru City Rumbai Subdistrict concerning the value of children’s education for parents of angkot drivers has been completed by drawing some conclusions as follows: Respondents most school children that is based on 2 people with percentage of 33.8%, which means that education is a right for children, then parents will seek to facilitate the educational supporting tool for smooth degree. Research finds the meaning of the education for the respondent is as follows: prepare a child to Get a job. The majority of respondents stated that the education of the future will determine the socioeconomic status of families of 70%, the Media to teach a social Role, the respondents agree with the response, as evidenced by the answers of the respondents amounted to 71 with percentage of 88.8%, Cultural transmission of Tool, more Respondents agree that the influence of the moral education effect on attitude of children in surroundings of 75 with the percentage of 93.8%. Correction of fate, the respondents strongly agree that economic influences have an effect on the level of education, as evidenced by the answers of the respondents amounted to 78 with percentage of 97.5%. Keywords: Value, Education, Children